Preparation method of core-shell hollow structure for photocatalytic particle self-nucleation
By surface modification of titanium dioxide nanospheres and synthesizing silica shells in micro-nano bubbles to form a core-shell hollow structure, the problem of surface area limitation of photocatalytic reactions is solved, the catalytic activity is improved and the preparation process is simplified.
Patent Information
- Application Number
- CN202280003369.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-02-22
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2042-02-22
AI Technical Summary
The catalytic reaction of existing photocatalytic materials mainly occurs on the surface of the material, resulting in a surface area limiting the catalytic effect, and the shell covering the core surface will interfere with catalytic activity.
By modifying the titanium dioxide nanospheres with surface hydrophobic substances to make them gas-averse, then placing them in a system of water and micro-nano bubbles, using the difference in affinity and surface tension, the titanium dioxide particles are driven into the micro-nano bubbles by themselves, and finally synthesizing the silica shell at the water-space interface of the micro-nano bubbles to form a core-shell hollow structure.
The active surface of the catalytic reaction is broadened, the catalytic activity is improved, and the raw materials are saved. The preparation process is relatively simple and the conditions are easy to control, which is suitable for large-scale industrial production.
Smart Images

Figure CN116940412B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of polymer materials, and in particular to a method for preparing a core-shell hollow structure of self-driven nucleation of photocatalytic particles. Background Art
[0002] Titanium dioxide is a common semiconductor photocatalytic material. Under the irradiation of light, it can convert light energy into chemical energy and decompose toxic and harmful organic matter in a relatively short time. In addition, it has the characteristics of high stability, light corrosion resistance, non-toxicity, and no secondary pollution during the treatment process. Therefore, it has attracted more and more attention in the fields of antibacterial, deodorization, oil decomposition, mildew and algae prevention, air purification, etc. However, since the catalytic reaction is essentially a surface contact reaction, it only occurs on the surface of the material. Therefore, for the catalyst, the limited surface area must be used for the catalytic reaction and at the same time bear the task of particle loading and fixing, which often greatly affects the catalytic effect.
[0003] The core-shell structure is an ordered assembly structure at the nanoscale formed by one nanomaterial encapsulating another nanomaterial through chemical bonds or other forces. It plays an important role in maintaining the functional stability of catalysts, adjusting the physical and chemical properties of materials to achieve complementary advantages, preventing nanoparticle agglomeration, and controlling particle interface reactions. It has broad application prospects in photocatalysis, batteries, gas storage and separation. However, for nanocatalytic materials that rely on surface area to promote reactions, how to solve the problem of the shell covering the core surface and interfering with the catalytic activity of the core has always been an unavoidable obstacle on the road to the application of nanocatalysts. Summary of the invention
[0004] The present disclosure aims to solve one of the technical problems in the related art at least to a certain extent. The present disclosure utilizes the surface interface principle that the surface hydrophobic material has aerophilicity, and uses tetra(octadecyl) orthotitanate to modify the surface hydrophobicity of commercially available titanium dioxide nanosphere particles. Then the titanium dioxide particles are placed in a system of water and micro-nano bubbles, and the titanium dioxide particles are self-driven into the micro-nano bubbles through the difference in aerophilic surface tension. Finally, a silicon dioxide shell is synthesized at the water-air interface of the micro-nano bubbles to obtain a photocatalytic core-shell hollow structure nanoparticle with a hollow structure between the core and the shell.
[0005] Specifically, the present disclosure provides the following technical solutions:
[0006] The first aspect of the present disclosure provides a method for preparing core-shell hollow structure nanoparticles, comprising:
[0007] (1) mixing an alcohol solution of titanium dioxide and tetra(octadecyl)orthotitanate to obtain a first solution, wherein the first solution contains modified titanium dioxide nanospheres;
[0008] (2) injecting air into water through a micro-nano bubble generator, shearing and crushing the water to obtain a second solution, wherein the second solution contains micro-nano bubbles;
[0009] (3) mixing the second solution and the first solution at a temperature above 35 degrees Celsius to obtain a third solution;
[0010] (4) adding ammonia water and tetraethyl orthosilicate solution to the third solution to obtain a fourth solution;
[0011] (5) separating, drying and calcining the precipitate to obtain core-shell hollow structure nanoparticles.
[0012] According to an embodiment of the present disclosure, the method for preparing the core-shell hollow structure nanoparticles described above may further include the following technical features:
[0013] Furthermore, the alcohol solution of titanium dioxide in step (1) contains 1 to 4 parts by weight of titanium dioxide, and the tetra(octadecyl)orthotitanate is 0.1 to 1.5 parts by weight.
[0014] Furthermore, the diameter of titanium dioxide in the alcohol solution of titanium dioxide in step (1) is 200 to 400 nanometers.
[0015] Furthermore, the alcohol solution of titanium dioxide in step (1) is an ethanol solution of titanium dioxide, which contains 1 to 4 parts by weight of titanium dioxide and 10 to 50 parts by weight of anhydrous ethanol.
[0016] Furthermore, the diameter of the micro-nano bubbles in step (2) is 600 to 1000 nanometers.
[0017] Furthermore, the shearing and crushing time is 4 to 9 hours.
[0018] Furthermore, in step (2), air is pumped into the water by a micro-nano bubble generator. According to a preferred embodiment of the present disclosure, air is pumped into the water by a micro-nano bubble generator so that the air humidity is 5% to 30%.
[0019] Furthermore, the temperature in step (3) is 40 degrees Celsius.
[0020] Furthermore, in step (4), based on the amount of titanium dioxide in step (1) being 1 to 4 parts by weight, the amount of ammonia water is 1 to 10 parts by weight, and the amount of ethyl orthosilicate solution is 2 to 10 parts by weight.
[0021] Furthermore, in step (5), the calcination temperature is 400 to 500 degrees Celsius, and the calcination time is 1 to 3 hours.
[0022] Furthermore, the drying temperature is 70 to 90 degrees Celsius.
[0023] The second aspect of the present disclosure provides a method for preparing core-shell hollow structure nanoparticles, comprising:
[0024] (1) mixing an alcohol solution of titanium dioxide and tetra(octadecyl)orthotitanate to obtain a first solution, wherein the first solution contains modified titanium dioxide nanospheres, and the alcohol solution of titanium dioxide contains 10 to 50 parts by weight of anhydrous ethanol and 1 to 4 parts by weight of titanium dioxide;
[0025] (2) injecting air into water through a micro-nano bubble generator, and performing shearing and crushing to obtain a second solution, wherein the second solution contains micro-nano bubbles, and the diameter of the micro-nano bubbles is 600-1000 nm;
[0026] (3) mixing the second solution and the first solution at 40 degrees Celsius to obtain a third solution;
[0027] (4) adding 1 to 10 parts by weight of aqueous ammonia and 2 to 10 parts by weight of ethyl orthosilicate solution to the third solution to obtain a fourth solution;
[0028] (5) separation, drying the precipitate and then calcining it to obtain core-shell hollow structure nanoparticles.
[0029] The third aspect of the present disclosure provides a core-shell hollow structure nanoparticle, which is prepared according to the method described in any one of the first aspect or the second aspect.
[0030] The beneficial effects achieved by the present disclosure are: photocatalytic core-shell hollow structure nanoparticles are obtained by the method provided by the present disclosure, and the core-shell hollow structure of the obtained nanoparticles broadens the active surface of the catalytic reaction, improves the activity, and can also save raw materials. The product preparation process is relatively simple, the conditions are easy to control, and it is easy to mass industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 is an electron microscope image of core-shell hollow structure nanoparticles provided according to an embodiment of the present disclosure.
[0032] Figure 2 It is an EDS electron energy spectrum diagram of the core-shell hollow structure nanoparticles provided according to the embodiments of the present disclosure.
[0033] Figure 3 It is the XRD data result of the core-shell hollow structure nanoparticles provided according to the embodiments of the present disclosure.
[0034] Figure 4 The photocatalytic fading experimental results of the Rhodamine B solution provided in the embodiments of the present disclosure are shown.
[0035] Figure 5 These are the antibacterial performance test results of Escherichia coli and Staphylococcus aureus provided according to the embodiments of the present disclosure.
[0036] Figure 6 It is an electron microscope result diagram provided according to Comparative Example 1 of the present disclosure.
[0037] Figure 7 This is an electron microscope result diagram provided according to Comparative Example 2 of the present disclosure.
[0038] Figure 8 This is an electron microscope result diagram provided by comparative particle 3 according to the present disclosure. DETAILED DESCRIPTION
[0039] Embodiments of the present disclosure are described in detail below with reference to the accompanying drawings. It should be noted that the embodiments shown are exemplary and are intended to be used to explain the present disclosure, but should not be construed as limiting the present disclosure.
[0040] Micro-nano bubbles are a special gas state existing at the interface between gas and liquid. They can exist stably in liquid for a long time and can be used as a non-contact preparation template for the catalyst surface. Micro-nano bubbles can be obtained by a commercially available micro-nano bubble generator. For example, the commercially available micro-nano bubbles are high shear generators, which generally use dynamic or static high-speed shear equipment to obtain micro-nano bubbles by breaking up large bubbles of gas-liquid mixture.
[0041] The present invention utilizes the surface interface principle that the hydrophobic substance has aerophilicity, places titanium dioxide particles with a surface modified to be hydrophobic in a system of water and micro-nano bubbles, and self-drives the titanium dioxide particles into the micro-nano bubbles through the difference in aerophilic surface tension. Finally, a silicon dioxide shell is synthesized at the water-air interface of the micro-nano bubbles to obtain a photocatalytic core-shell hollow structure nanoparticle with a hollow structure between the core and the shell.
[0042] The present disclosure provides a method for preparing core-shell hollow structure nanoparticles, comprising:
[0043] (1) mixing an alcohol solution of titanium dioxide and tetra(octadecyl)orthotitanate to obtain a first solution, wherein the first solution contains modified titanium dioxide nanospheres;
[0044] (2) injecting air into water through a micro-nano bubble generator, shearing and crushing the water to obtain a second solution, wherein the second solution contains micro-nano bubbles;
[0045] (3) mixing the second solution and the first solution at a temperature above 35 degrees Celsius to obtain a third solution;
[0046] (4) adding ammonia water and tetraethyl orthosilicate solution to the third solution to obtain a fourth solution;
[0047] (5) separating, drying and calcining the precipitate to obtain core-shell hollow structure nanoparticles.
[0048] There is no special requirement for the preparation order of step (1) and step (2).
[0049] According to a specific embodiment, the alcohol solution of titanium dioxide in step (1) contains 1 to 4 parts by weight of titanium dioxide, and the tetra(octadecyl) orthotitanate is 0.1 to 1.5 parts by weight. The appropriate content of tetra(octadecyl) orthotitanate can play a role in surface hydrophobic modification, thereby obtaining modified titanium dioxide nanospheres.
[0050] According to a specific implementation, the diameter of titanium dioxide in the alcohol solution of titanium dioxide in step (1) is 200 to 400 nanometers.
[0051] According to a specific embodiment, the alcohol solution of titanium dioxide in step (1) is an ethanol solution of titanium dioxide, which contains 1 to 4 parts by weight of titanium dioxide and 10 to 50 parts by weight of anhydrous ethanol.
[0052] According to a specific embodiment, the diameter of the micro-nano bubbles in step (2) is 600-1000 nanometers, for example, 700-1000 nanometers, 800-1000 nanometers, 900-1000 nanometers, 600-800 nanometers. The diameter of the micro-nano bubbles will directly affect the performance of the core-shell hollow structure nanoparticles finally prepared and the size of the space between the core and the shell formed. If the micro-nano bubbles are too small, it will affect the loading of the core-shell hollow structure nanoparticles. If the diameter of the micro-nano bubbles is too large, the shell structure of the core-shell hollow structure nanoparticles finally formed will be unstable.
[0053] According to a specific embodiment of the present disclosure, the shearing and crushing time is 4 to 9 hours.
[0054] According to a specific embodiment of the present disclosure, in step (2), air is pumped into water through a micro-nano bubble generator.
[0055] According to a specific embodiment of the present disclosure, the temperature in step (3) is 40 degrees Celsius. As the alcohol evaporates, the titanium dioxide nanospheres with hydrophobic surface modification will produce hydrophobic and aerophilic properties due to the effect of surface tension, and then self-drive into the interior of the bubbles (similar to the process of removing impurities from bubbles in water).
[0056] Tetraethyl orthosilicate can form silicon dioxide under the action of ammonia water. According to a specific embodiment of the present disclosure, in step (4), the amount of titanium dioxide in step (1) is 1 to 4 parts by weight, the amount of ammonia water is 1 to 10 parts by weight, and the amount of tetraethyl orthosilicate solution is 2 to 10 parts by weight.
[0057] According to a specific embodiment of the present disclosure, the calcination temperature in step (5) is 400 to 500 degrees Celsius, and the calcination time is 1 to 3 hours.
[0058] According to a specific embodiment of the present disclosure, the drying temperature is 70 to 90 degrees Celsius.
[0059] The present disclosure is further described below in conjunction with the examples. The examples are for illustration only and are not intended to limit the present disclosure. The scheme of the present disclosure will be explained below in conjunction with the examples. Those skilled in the art will appreciate that the following examples are only intended to illustrate the present disclosure and should not be construed as limiting the scope of the present disclosure. If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the art or in accordance with the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0060] Example 1
[0061] Embodiment 1 provides a method for preparing a core-shell hollow structure nanoparticle, comprising:
[0062] 2 parts by weight of commercially available titanium dioxide nanospheres with a diameter of about 200-400 nm were added to 1.30 parts by weight of anhydrous ethanol and stirred evenly.
[0063] 2. Add 1 part by weight of tetra(octadecyl)orthotitanate to the solution obtained in step 1 above, and stir for 24 hours to modify the surface hydrophobicity of the titanium dioxide nanospheres.
[0064] 3. Use a commercially available micro-nano bubble generator to inject air into 100 parts by weight of distilled water, and obtain micro-nano bubbles by shearing and breaking the gas and liquid. The diameter of the micro-nano bubbles is controlled at about 800 nm, and the shearing time is 6 hours.
[0065] 4. After heating the solution obtained in step 3 to 40 degrees Celsius, quickly add 10 parts by weight of the solution obtained in step 2.
[0066] 5. Add 5 parts by weight of aqueous ammonia to the solution obtained in step 4, stir vigorously, then dropwise add 5 parts by weight of ethyl orthosilicate solution, and stir for 4 hours.
[0067] 6. Finally, the solution obtained in step 5 is centrifuged to separate the precipitate, which is then dried at 80 degrees Celsius for 12 hours and then calcined at 400-500 degrees Celsius for 1-3 hours to obtain core-shell hollow structure nanoparticles.
[0068] The electron microscope images of the obtained core-shell hollow structure nanoparticles are shown in Figure 1 shown.
[0069] The prepared core-shell hollow structure nanoparticles were characterized by EDS electron energy spectrum. Figure 2 As shown, Figure 2 EDS electron energy spectrum shows the proportion of each component element of the core-shell hollow structure nanoparticles as photocatalysts.
[0070] In addition, XRD data showed that the lattice structure of titanium dioxide particles in the core-shell hollow structure nanoparticles did not change, showing standard anatase phase titanium dioxide lattice structure parameters, such as Figure 3 shown.
[0071] The photocatalytic fading experimental results of Rhodamine B solution are as follows Figure 4 As shown, the results also show that the core-shell hollow structure nanoparticles can photocatalytically decolorize 1x10-5mol / L Rhodamine B (RhB) solution within 1 hour, and its catalytic activity is higher than that of untreated titanium dioxide particles under the same conditions.
[0072] The antibacterial test results of Escherichia coli and Staphylococcus aureus are as follows Figure 5 As shown, the results also showed that the blank sample ( Figure 5 Numbers 1 and 2 in Figure b) and the titanium dioxide sample ( Figure 5 Compared with No. 3 and No. 4 in Figure b, the sample with core-shell hollow nanoparticles added ( Figure 5 Numbers 5 and 6 in Figure b) showed the highest antibacterial properties.
[0073] Example 2
[0074] Embodiment 2 provides a method for preparing a core-shell hollow structure nanoparticle, comprising:
[0075] 4 parts by weight of commercially available titanium dioxide nanospheres with a diameter of about 200-400 nm were added to 1.50 parts by weight of anhydrous ethanol and stirred evenly.
[0076] 2. Add 1.5 parts by weight of tetra(octadecyl)orthotitanate to the solution obtained above and stir for 40 hours to modify the surface hydrophobicity of the titanium dioxide nanospheres.
[0077] 3. Use a commercially available micro-nano bubble generator to inject air into 100 parts by weight of distilled water, and obtain micro-nano bubbles by shearing and breaking the gas and liquid. The diameter of the micro-nano bubbles is controlled at about 1000 nm, and the shearing time is 8 hours.
[0078] 4. After heating the solution obtained in step 3 to 40 degrees Celsius, quickly add 20 parts by weight of the solution obtained in step 2.
[0079] 5. Add 10 parts by weight of aqueous ammonia to the solution described in step 4, stir vigorously, then dropwise add 10 parts by weight of ethyl orthosilicate solution, and stir for 4 hours.
[0080] 6. Finally, the solution obtained in step 5 is centrifuged to separate the precipitate, which is then dried at 80 degrees Celsius for 12 hours and then calcined at 400-500 degrees Celsius for 1-3 hours to obtain core-shell hollow structure nanoparticles.
[0081] The core-shell hollow structure nanoparticles prepared in Example 2 were characterized in the same manner as in Example 1, and showed similar characteristics to the core-shell hollow structure nanoparticles prepared in Example 1.
[0082] Comparative Example 1
[0083] During the experiment, it was found that when the surface of titanium dioxide nanospheres is hydrophobically modified, if tetra(octadecyl) orthotitanate is not used, the surface hydrophobicity will be insufficient, resulting in the inability to form the surface tension effect provided by the present disclosure, produce hydrophobic and air-philic properties, and self-drive into the interior of the bubble, resulting in the absence of a core in the final formed silica shell. Figure 6 Similarly, if the amount of tetra(octadecyl)orthotitanate is insufficient, the structure and performance of the formed core-shell hollow structure nanoparticles will also be affected.
[0084] Comparative Example 2
[0085] During the research, it was found that when tetraethyl orthosilicate was used to synthesize silica shells at the water-air interface using ammonia water, the silica reaction was too fast, resulting in the inability to form a shell structure. Figure 7 Therefore, when adding the orthosilicic acid ethanol solution, it should be added dropwise.
[0086] Comparative Example 3
[0087] During the research, it was found that when ethyl orthosilicate is used to synthesize silica shell at the water-air interface by the action of ammonia water, if too much ethyl orthosilicate solution is added, it will lead to excess silica in the system, resulting in silica self-agglomeration, which will affect the formation of normal shell structure. Figure 8 shown.
[0088] The above is only a preferred embodiment of the present disclosure. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present disclosure. These improvements and modifications should also be considered as the scope of protection of the present disclosure.
Claims
1. A method for preparing core-shell hollow structure nanoparticles, characterized in that: include: (1) mixing an alcohol solution of titanium dioxide and tetra(octadecyl)orthotitanate to obtain a first solution, wherein the first solution contains modified titanium dioxide nanospheres; (2) injecting air into water through a micro-nano bubble generator, shearing and crushing the water to obtain a second solution, wherein the second solution contains micro-nano bubbles; the diameter of the micro-nano bubbles is 600 to 1000 nanometers; (3) mixing the second solution and the first solution at a temperature above 35 degrees Celsius to obtain a third solution; (4) adding ammonia water and tetraethyl orthosilicate solution to the third solution to obtain a fourth solution; (5) separation, drying the precipitate and then calcining it to obtain core-shell hollow structure nanoparticles.
2. The method according to claim 1, characterized in that The alcohol solution of titanium dioxide in step (1) contains 1 to 4 parts by weight of titanium dioxide, and the tetra(octadecyl)orthotitanate is 0.1 to 1.5 parts by weight.
3. The method according to claim 1, characterized in that The diameter of titanium dioxide in the alcohol solution of titanium dioxide in step (1) is 200 to 400 nanometers.
4. The method according to claim 1, characterized in that: The alcohol solution of titanium dioxide in step (1) is an ethanol solution of titanium dioxide, which contains 1 to 4 parts by weight of titanium dioxide and 10 to 50 parts by weight of anhydrous ethanol.
5. The method according to claim 1, characterized in that The shearing and crushing time is 4 to 9 hours.
6. The method according to claim 1, characterized in that In step (2), air is pumped into water through a micro-nano bubble generator to make the air humidity 5% to 30%.
7. The method according to claim 1, characterized in that The temperature in step (3) is 40 to 50 degrees Celsius.
8. The method according to claim 1, characterized in that In step (4), based on the amount of titanium dioxide in step (1) being 1 to 4 parts by weight, the amount of ammonia water is 1 to 10 parts by weight, and the amount of ethyl orthosilicate solution is 2 to 10 parts by weight.
9. The method according to claim 1, characterized in that: The calcination temperature in step (5) is 400 to 500 degrees Celsius, and the calcination time is 1 to 3 hours.
10. The method according to claim 1, characterized in that The drying temperature is 70 to 90 degrees Celsius.
11. A method for preparing core-shell hollow structure nanoparticles, characterized in that: include: (1) mixing an alcohol solution of titanium dioxide and tetra(octadecyl)orthotitanate to obtain a first solution, wherein the first solution contains modified titanium dioxide nanospheres, and the alcohol solution of titanium dioxide contains 10 to 50 parts by weight of anhydrous ethanol and 1 to 4 parts by weight of titanium dioxide; (2) injecting air into water through a micro-nano bubble generator, and performing shearing and crushing to obtain a second solution, wherein the second solution contains micro-nano bubbles, and the diameter of the micro-nano bubbles is 600-1000 nm; (3) mixing the second solution and the first solution at 40 degrees Celsius to obtain a third solution; (4) adding 1 to 10 parts by weight of aqueous ammonia and 2 to 10 parts by weight of ethyl orthosilicate solution to the third solution to obtain a fourth solution; (5) separation, drying the precipitate and then calcining it to obtain core-shell hollow structure nanoparticles.
12. A core-shell hollow structure nanoparticle, characterized in that: Prepared according to the method according to any one of claims 1 to 11.
Citation Information
Patent Citations
Method for preparing interface optical catalyst
CN101099929A
Efficient sterilization photocatalyst material used for indoor air purification, and preparation method thereof
CN109221251A